2009
DOI: 10.1021/jp905357a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Conformational Movement and Radical Mechanism in the Reaction of 4-Thia-l-lysine with Lysine 5,6-Aminomutase

Abstract: We demonstrate that the steady state reaction of lysine 5,6-aminomutase with substrate analogue 4-thia-l-lysine generates a radical intermediate, which accumulates in the enzyme to an electron paramagnetic resonance (EPR) detectable level. EPR line width narrowing of approximately 1 mT due to [4'-(2)H] labeling of the pyridoxal-5'-phosphate (PLP), an isotropic hyperfine coupling of 40 MHz for the proton at C4' of PLP derived from (2)H electron nuclear double resonance (ENDOR) measurement, and spin density delo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…The lack of complete conversion of the enzyme to this radical (see Figure 6) and the absence of a long wavelength absorbance (see Figure 7) are inconsistent with the quinonoid form. In addition, the magnitude of the PLP-C4′(H) hyperfine coupling calculated for the quinonoid radical 7 is smaller than the observed value (Table 2) (15). …”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The lack of complete conversion of the enzyme to this radical (see Figure 6) and the absence of a long wavelength absorbance (see Figure 7) are inconsistent with the quinonoid form. In addition, the magnitude of the PLP-C4′(H) hyperfine coupling calculated for the quinonoid radical 7 is smaller than the observed value (Table 2) (15). …”
Section: Resultsmentioning
confidence: 75%
“…Reaction of 4-thia- d -lysine leads to analogous radicals on a faster time scale (Supplemental Information). Deuterium labeling in the carboxaldehyde group of PLP (C4′) narrows the signal (15), clearly showing hyperfine coupling of PLP-C4′–H with the unpaired electron in the persistent species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of 4,5-OAM, the evidence for radical mechanism was obtained using a substrate homologue [9]. Identification of corresponding S Å in the reaction of 5,6-LAM has been reported recently [10,11] using substrate analogue 4-thialysine. The characterization of that was confirmed by electron paramagnetic resonance (EPR) and electron nuclear double resonance (ENDOR) spectroscopic studies [12] on isotopeedited substrate analogues, 4-thia-[5-13 C]lysine [13] and 4-thia-[6-13 C]lysine [14].…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, they proposed that the reaction of 4-thialysine with 5,6-LAM would accumulate the corresponding substrate related radical to required concentration for EPR detection. In fact, evidence for the radical mechanism was recently reported by using substrate analogue 4-thialysine [27,28]. Tang et al reported the observation of two different radicals and proposed the presence of transient radical, which is the corresponding substrate related radical, and persistent radical [28].…”
Section: Introductionmentioning
confidence: 99%